Roles of benefit finding in psychological and inflammatory adjustments in persons with colorectal cancer: a prospective analysis on the multidimensionality of benefit finding. - Tsai, Thomas C.; Lee, Gabriela G.; Ting, Amanda; Antoni, Michael H.; Mendez, Armando; Carver, Charles S.; Kim, Youngmee (Psychology & Health, 2025)
Objective: This study examined the unique associations of different dimensions of the resilience factor, benefit finding, on concurrent and prospective psychological and biological adjustment outcomes over the first year after a colorectal cancer diagnosis. Methods and measures: Individuals newly diagnosed with colorectal cancer (n = 133, mean age = 56 years old, 59% female, 46% Hispanic) completed questionnaires assessing the multidimensional aspects of benefit finding around 4 months post-diagnosis (T1). Psychological (depressive symptoms and life satisfaction) and biological [C-reactive protein (CRP) and interleukin-10 (IL-10)] adjustments were assessed at T1 and one-year post-diagnosis (T2). Results: Structural equation modeling revealed that at T1, greater reprioritization was concurrently related to higher depressive symptoms (p=.020). Lower acceptance, lower empathy, and greater positive self-view predicted higher life satisfaction at T2 (ps<.010). Additionally, lower empathy and greater family valuation predicted higher CRP at T2 (ps<.004), whereas greater positive self-view predicted higher IL-10 at T2 (p=.039). Greater overall benefit finding was associated with lower IL-10 at T1 (p=.013). Conclusion: Various aspects of benefit finding differentially relate to psychological and inflammatory markers during the first year after diagnosis in persons with colorectal cancer. Interventions designed to specifically enhance positive self-view may promote both the psychological and biological health of individuals with cancer.